171k views
4 votes
Find the average rate of change of the function from
x_(1)= 1 to
x_(2) = 5.​

Function =
x^(2) - 4x + 10

User Krillgar
by
4.9k points

1 Answer

7 votes

Hi there!


\large\boxed{\text{Average rate} = 2}

Use the following equation to solve:


\text{Average rate} = (f(x_(2)) - f(x_(1)))/(x_(2) - x_(1))

Solve for the y-values of the equation at the given x values:

f(1) = 1² - 4(1) + 10 = 7

f(5) = 5² - 4(5) + 10 = 15

Plug the solved values into the equation:


\text{Average rate} = (15 - 7)/(5-1)

Simplify:


\text{Average rate} = (8)/(4) = 2

User Wasif Kirmani
by
5.2k points